Evaluation and Reliability of Mangled Extremity Severity Scoring in Traumatic Amputation Versus Limb Salvage (Journal of Pakistan Orthopaedic Association, 2013)
Introduction: To salvage or amputate a severely injured limb is one of the most difficult decisions an orthopaedic surgeon may face. Several scoring system have been proposed for it. Observing paucity of any Pakistani study, we analyzed predictability of amputation or salvage in an extremity by using Mangled extremity severity score.Objective: To determine the clinical utility of MESS in predicting limb salvage versus primary amputation.Study Design: Prospective descriptive study. Setting: Orthopaedics department, Jinnah Postgraduate Medical Center, Karachi.Subjects & Methods: 50 consecutive patients with 52 mangled extremities of either sex or any age admitted between May2005 to July2008 were included. MESS used to assist in the decision–making process. Results: High energy trauma (86%)was commonest mechanism of injury. Out of 52injured limbs, 38 (73.1%) with a MESS score of equal or more than 7 were amputated while remaining 14 (29.9%) with MESS less than 7 in which 12 (23.1%) were successfully salvaged and 2 (3.84%) were amputated. Mean score for amputated limbs was 8.67±0.83 & salvaged limb was 3.07±0.99. Mean MESS score of amputated limbs was significantly high than salvaged limbs (p=0.0001). MESS could predict amputation of severely injured lower limbs, having score of equal and more than 7 with 95%sensitivity, 100% specificity, 100 % positive predictive value & 85.7% negative predictive value. Conclusion: MESS, a relatively simple & objective scoring system is highly accurate in the predictability of limb viability in patients with lower extremity trauma. Keywords: Mangled extremity, MESS, scoring system.